Transposer l’ironie théâtrale dans la langue de l’Autre. Le cas de La Cantatrice chauve d’Ionesco en grec - Constantinou, Maria (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper sets out to examine the challenges involved in translating irony in a theatrical play by Eugene Ionesco (La cantatrice chauve) into Greek. The study is based on two officially published translations by Protopapas (1987) and Errikos Belies (2007) respectively. On the one hand, it endeavours to look into the function of ironical effects and networks within the original play, and on the other hand it tries to explore the challenge involved in transposing the ironical effects and networks and the degree of “ironicity” present in the translated texts. To begin with, some definitions of irony as a thought and rhetorical figure are reviewed from a theoretical point of view and in relation to Ionesco ’s work and ethos. The study relies on theoretical insights in the field of theatrical translation and proposes a pragm atico-textual approach to the phenomenon of irony in both the original and the translated texts.